Women’s Involvement In Entrepeneurship In Pasar Besar Siti Khadijah Kota Bharu Kelantan: A Study About Successful Factors In Handling Business / Mohd Ammar Daud and Mohd Airjuddin Talib - Talib, Mohd Airjuddin; Daud, Mohd Ammar (2010)
This study examines and identifies the factors that influence women to get involve in entrepreneurship and the successful factors of their business itself. Other than that, this study also to identify the relationship between personal profile and business background profile that encourage Kelantanese women entrepreneurs to get involved in entrepreneurship. Furthermore, the perception of women regarding the factors that lead them to be success in handling business among Kelantanese women at Pasar Besar Siti Khadijah, Kota Bharu Kelantan. The findings give details about the relationships and how women entrepreneurs can use this study to improve their performance, achievement and recognize the successful factors of their business. This study also provides guidelines for future researchers to do research based on this particular topic.